Tick salivary gland extract induces alpha‐gal syndrome in alpha‐gal deficient mice. Issue 3 (25th May 2021) - Choudhary, Shailesh K.; Karim, Shahid; Iweala, Onyinye I.; Choudhary, Shivangi; Crispell, Gary; Sharma, Surendra Raj; Addison, Claire T.; Kulis, Mike; Herrin, Brian H.; Little, Susan E.; Commins, Scott P.
Abstract: Introduction: Alpha‐gal syndrome (AGS) is characterized by delayed hypersensitivity to non‐primate mammalian meat in people having specific immunoglobulin E (sIgE) to the oligosaccharide galactose‐alpha‐1, 3‐galactose. AGS has been linked to tick bites from Amblyomma americanum ( Aa ) in the U.S. A small animal model of meat allergy is needed to study the mechanism of alpha‐gal sensitization, the effector phase leading to delayed allergic responses and potential therapeutics to treat AGS. Methods: Eight‐ to ten‐weeks old mice with a targeted inactivation of alpha‐1, 3‐galactosyltransferase (AGKO) were injected intradermally with 50 μg of Aa tick salivary gland extract (TSGE) on days 0, 7, 21, 28, 42, and 49. Total IgE and alpha‐gal sIgE were quantitated on Day 56 by enzyme‐linked immunosorbent assay. Mice were challenged orally with 400 mg of cooked pork kidney homogenate or pork fat. Reaction severity was assessed by measuring a drop in core body temperature and scoring allergic signs. Results: Compared to control animals, mice treated with TSGE had 190‐fold higher total IgE on Day 56 (0.60 ± 0.12 ng/ml vs. 113.2 ± 24.77 ng/ml; p < 0.001). Alpha‐gal sIgE was also produced in AGKO mice following TSGE sensitization (undetected vs. 158.4 ± 72.43 pg/ml). Further, sensitized mice displayed moderate clinical allergic signs along with a drop in core body temperature of ≥2°C as an objective measure of a systemic allergic reaction. Interestingly, female mice had higher total IgE responses to TSGE treatment but male mice had larger declines in mean body temperature. Conclusion: TSGE‐sensitized AGKO mice generate sIgE to alpha‐gal and demonstrate characteristic allergic responses to pork fat and pork kidney. In keeping with the AGS responses documented in humans, mice reacted more rapidly to organ meat than to high fat pork challenge. This mouse model establishes the central role of tick bites in the development of AGS and provides a small animal model to mechanistically study mammalian meat allergy. Abstract : Alpha‐gal syndrome (AGS) is characterized by delayed hypersensitivity to non‐primate mammalian meat in people having specific IgE (sIgE) to the oligosaccharide galactose‐alpha‐1, 3‐galactose and has been linked to tick bites from Amblyomma americanum (Aa) in the U.S. We demonstrate that intradermal injection of Aa tick salivary gland extract (TSGE) in alpha‐gal knockout (AGKO) mice induce alpha‐gal sIgE production and mice displayed moderate clinical allergic signs along with a drop in core body temperature as an objective measure of a systemic allergic reaction. Further, this model recapitulates several aspects of red meat allergy seen in the humans and will be used to mechanistically study this novel food allergy and model therapeutic approaches to treat this disease.